Credit-related Shocks in VAR Models: The Case of Lithuania - Reichenbachas, Tomas (Ekonomika, 2018)
This article provides empirical evidence on the role played by credit-related shocks over the business cycle in Lithuania. To this end, we estimate a vector auto regression (VAR) with credit and housing variables and identify credit-related shocks. Using sign restriction, we identify credit supply shocks; while using zero restrictions, we identify credit spread shocks. We find evidence that credit-related shocks have a significant effect on housing and credit market variables, while the effect on GDP is less pronounced but still significant. While credit supply shocks weighed down on economic growth during the period from 2008 to 2014, the effect turned positive in 2014.